Impacts of Court Ruling on Digital Democracy and Free Expression - Ikawati, Linda; Mardani, Retno Eko; Saraya, Sitta; Putra, Rengga Kusuma (Jurnal Ilmiah Dunia Hukum, 2025)
This study aims, first, to analyze the legal reasoning of the Constitutional Court in Decision Number 115/PUU-XXII/2024, which annulled the phrase "riots" in Article 28 paragraph (3) and Article 45A paragraph (3) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions. Second, it seeks to examine the implications of this annulment for the scope of freedom of expression and the potential regulation of hate speech or incitement in Indonesia's digital sphere. It further explores how this Constitutional Court decision may influence the dynamics of digital democracy, particularly in the context of public criticism and online participation in Indonesia. This study employs a qualitative research method, with the primary legal material being Constitutional Court Decision Number 115/PUU-XXII/2024 on the Judicial Review of Provisions in Law Number 1 of 2024. The findings reveal that the Constitutional Court's removal of the phrase "riots" has the potential to broaden the space for digital freedom of expression, but it also presents new challenges in maintaining public order. Therefore, a deeper understanding of the boundaries of freedom of expression in the digital age is required, along with the development of effective legal and non-legal mechanisms to balance expressive freedom and social order.